Philosophy as Creator of Student Intellectual - Nufaris Elisa; Ismed Batubara (Britain International for Academic Research (BIAR) Publisher, 2019)
In this modern phase, it was thicked that in lerning the philosophy, there are two methods, namely: First, by history lerning, it has been developing since formerly period until nowadays. In this faced curriculum vitae of famed philosophers, with coming current or philosophy understanding in every problem, their ideas about logic, metaphysics, ethics and religion that talked chronologically according to each time. Second, with content learning methods, namely field learning that regulated in certain sector, such as ethica was confinnated according to ideas from classic period of Greek (Plato, Aristotle) ​​with ideas of philosophers in middle ages (Thomas Aquinas, Al Farabi) with ideas of philosophers in aufklarung period (Immanuel Kant) with ideas of philosophers in nowadays (Jasfer, Marsel) with out problem order each divisions. Presentation of this subject can lead to more progress than others, until they are clever in learning it. Eventually they become intellectual-smart